Physiological and biochemical changes during the loss of desiccation tolerance in millet (Pennisetum glaucum L.) seeds - Joana Souza Fernandes; Renato Mendes Guimarães; Jose Marcio Rocha Faria; Diego de Sousa Pereira; Stefania Vilas Boas Coelho; Ariadne Santos Oliveira (Acta Scientiarum: Agronomy, 2019)
The aim of this study was to evaluate the physiological and biochemical changes related to the loss of desiccation tolerance in millet seeds. The points studied were determined according to the seed imbibition curve of the hybrid ADRF6010: control (0 h), 3 h, 1 and 3 mm of radicle. The seeds were dried on silica gel for 72 h at 20 °C, followed by pre-humidification at 25 °C for 24 h. The physiological quality was evaluated by the electrical conductivity and germination test, and the seed vigor through the first count and germination speed index. The experiment was performed in a completely randomized design and means were compared by the Scott-knott test at 5% probability. The enzymatic systems evaluated were: superoxide dismutase, catalase, peroxidase, and α-amylase, and the expression of heat-resistant proteins. The enzymatic activity was quantified through the software ImageJ®. Millet seeds lost desiccation tolerance when the radicle reaches 1 mm of length. According to the enzymatic standards, the enzymes peroxidase and α-amylase, as well as the activity of heat-resistant proteins are related to the loss of desiccation tolerance in millet seeds.